Declining fitness and physical education lessons in UK adolescents. Issue 1 (18th January 2022) - Weedon, Benjamin David; Liu, Francesca; Mahmoud, Wala; Burden, Samuel Joseph; Whaymand, Luke; Esser, Patrick; Collett, Johnny; Izadi, Hooshang; Joshi, Shawn; Meaney, Andy; Delextrat, Anne; Kemp, Steve; et al.
Abstract : Objectives: The objective was to determine recent cross-sectional trends in health-related fitness (HRF) in secondary school students by studying the 13–14 years old age group repeatedly over 6 years, considering parallel national trends in physical education (PE). Methods: Height, weight, broad jump, grip strength, 20 m shuttle run and throwing and catching skills were measured by the same research team using standardised techniques from 2014 to 2019. Trends in these HRF measures were assessed by linear regression, adjusting for school, sex and height. Interactions with fitness and body mass index (BMI) were tested. The number of PE lessons reported in the UK Annual School Workforce Census between 2010 and 2019 for all state-funded secondary schools was analysed. Results: Grip strength ( B =−0.60, 95% CI −0.78 to –0.41), broad jump ( B =−1.16, 95% CI −1.99 to –0.34), 20 m shuttle run ( B =−1.85, 95% CI −2.58 to –1.12) and throwing and catching skills ( B =−0.12, 95% CI −0.15 to –0.08) declined significantly over the study period. There was a greater reduction in broad jump and grip strength in adolescents with low fitness and a greater reduction in fitness and motor competence in adolescents with normal BMI. These declines coincided with a 16% reduction nationally in secondary school PE between 2010 (333 800 hours) and 2019 (280 725 hours). Conclusion: Adolescent HRF has declined in recent years, in parallel with PE lessons. Declines were observed across all young people and particularly those of low fitness and normal BMI. To reach the majority of young people, policy makers could increase PE in schools to increase activity and prevent worsening fitness and health in future generations.